An experimental study on the effects of minimum profit share on supply chains with markdown contract: Risk and profit analysis. (December 2015) - Chow, Pui-Sze; Wang, Yulan; Choi, Tsan-Ming; Shen, Bin
Abstract: Supply chain performance measures include both profit and risk. In this study, we examine the effect of retailers' minimum profit share concerns on supply chain system performance through laboratory experimental and analytical modeling approaches. In the experiment, each retailer's minimum profit share, which partially reflects her self-serving fairness concern, is measured with a parameter defined as the minimum profit share ratio (MPSR), which is the ratio of the retailer's profit to the whole supply chain profit. We specifically consider a two-stage supply chain in which a supplier offers a take-it-or-leave-it markdown contract to a retailer who has an MPSR concern. In our laboratory experiment, the role of the supplier is played by human subjects who are practitioners in the fashion industry; to ensure that the MPSR concept is fully implemented, the role of the retailer is played by the computer. Mirroring the observed industrial practice, the markdown price is defined as a fixed percentage of the wholesale price, and the supplier needs to decide on a wholesale price. Our empirical results show that when the MPSR increases, the supplier's average profit and absolute risk decreases, whereas those of the retailer increase. As for the whole supply chain, our experiments suggest there is an inverse U-shaped relationship between the supply chain profit and the MPSR; thus the presence of an MPSR concern leads to a higher supply chain risk (both in absolute and relative terms). We also observe that when the retailer tends to split the supply chain profit equally with the supplier (MPSR=0.5; in this case, neither party faces disadvantageous inequality), the whole supply chain achieves the best performance, and the supply chain profit is close to the theoretically optimal one (the centralized supply chain profit). In other words, a fair retailer helps to create a sense of cooperation between the supplier and herself. Highlights: Explore the impacts of retailer's minimum profit sharing ratio (MPSR). An increased MPSR leads to a decrease of supplier's profit and risk. An increased MPSR yields increased retailer's profit and risk. An inverse U-shaped relationship exists between supply chain profit and MPSR. MPSR leads to a higher supply chain risk in both absolute and relative terms.